PENGARUH TINGKAT PENDIDIKAN TERHADAP KINERJA KARYAWAN HOUSEKEEPING DI HOTEL ROCKY PLAZA PADANG - Pratama, Jefilo Andas (journal of residu, 2019)
This study aims to determine the effect of education level on the performance of housekeeping employees at Rocky Plaza Padang Hotel. This type of research is classified into quantitative research with associative causal methods using simple linear regression tests. The population in this study were all housekeeping employees at the Rocky Plaza Padang Hotel, which numbered 30 people. The sample in this study amounted to 30 housekeeping employees at Rocky Plaza Padang Hotel with the sampling technique being saturated samples. Data collection techniques were carried out using a questionnaire (questionnaire) using the Guttman scale which had been tested for validity and reliability. Data were analyzed by simple linear regression test with the help of SPSS version 16.00. The results showed that: 1) Education Level Rocky Plaza Padang housekeeping employees are in the good category (80%), 2) The performance of the housekeeping staff of Rocky Plaza Hotel is in the bad category (80%), 3) Simple linear regression test results significance of 0.208 > 0.05, there is no positive and significant influence between the level of education and the performance of housekeeping employees with a r value of 0.237 with an interpretation of non-significant effects